PENAMBAHAN AUKSIN DAN SITOKININ TERHADAP PERTUMBUHAN TUNAS DAN AKAR GAHARU (Aquilaria malaccensis Lamk) SECARA IN VITRO In Vitro Addition of Auxin and Cytokinin to Growth of sShoot and Root of Gaharu (Aquilaria malaccensis Lamk) - tutthoyyibah, Warda; Wulandari,, Reine Suci; Darwati, Herlina (JURNAL HUTAN LESTARI, 2015)
ABSTRACT Gaharu (Aquilaria malaccensis L) is one of the non timber forest products (HHBK) has high-value commercial. The high value caused the demand for commodities is increasing every year. But it is inversely proportional to its availability in nature. This research aims to determine the best concentration of the addition of NAA, BAP and the combination between the NAA and BAP on growth of root and shoot of gaharu. The benefits of this research are expected to be a reference in the provision of seedlings with vegetative reproduction in agarwood technique of tissue culture, to support the procurement activities of the seeds in a sufficient amount of a good quality in a relatively short time, and the resulting seedlings were uniform. The methods used factorial experimental design of Randomized complete (RAL) consisting of two factors and three times in Deuteronomy. NAA factor consists of five degrees of treatment i.e. N0 = 0 mg/l, N1 = 1 mg/l, N2 = 2 mg/l, N3 = 3 mg/l and N4 = 4 mg/l, whereas the factor of BAP is also composed of five degrees of concentration i.e. B0 = 0 mg/l, B1 = 0.5 mg/l, B2 = 1 mg/l, B3 = 1.5 mg/l and B4 = 2 mg/l with three times the replay so that required 75 eksplan gaharu. The results showed the best NAA concentration in the added of shoots with a concentration of 0 mg/l NAA, while concentration of    3 mg/l NAA was the best concentration of length the shoots and growth added root gaharu. The best concentration of BAP on shoot length and added long shoots are concentration of 0,5 mg/l BAP, while concentration of 0 mg/l BAP is the best concentration of the growth roots gaharu. Key words :     Naphthalene acetic acid, benzyl amino purine, growth hormone, subcultures and aquilaria malaccensis.